2017
DOI: 10.1371/journal.pone.0169926
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Optics Reveals Photoreceptor Abnormalities in Diabetic Macular Ischemia

Abstract: Diabetic macular ischemia (DMI) is a phenotype of diabetic retinopathy (DR) associated with chronic hypoxia of retinal tissue. The goal of this prospective observational study was to report evidence of photoreceptor abnormalities using adaptive optics scanning laser ophthalmoscopy (AOSLO) in eyes with DR in the setting of deep capillary plexus (DCP) non-perfusion. Eleven eyes from 11 patients (6 women, age 31–68), diagnosed with DR without macular edema, underwent optical coherence tomography angiography (OCTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 44 publications
3
68
0
5
Order By: Relevance
“…14,51,59 In these studies, as in ours, nonperfusion in the retinal vasculature was associated with the observed photoreceptor mosaic abnormalities, but they were not present in all regions with nonperfusion further supporting the likelihood of an additional factor influencing photoreceptor changes in diabetics. This additional factor may be colocalized nonperfusion in the choriocapillaris 58 or localized areas of breakdown of the outer blood retinal barrier 60,61 compromising the outer retinal layers.…”
Section: Discussionsupporting
confidence: 70%
“…14,51,59 In these studies, as in ours, nonperfusion in the retinal vasculature was associated with the observed photoreceptor mosaic abnormalities, but they were not present in all regions with nonperfusion further supporting the likelihood of an additional factor influencing photoreceptor changes in diabetics. This additional factor may be colocalized nonperfusion in the choriocapillaris 58 or localized areas of breakdown of the outer blood retinal barrier 60,61 compromising the outer retinal layers.…”
Section: Discussionsupporting
confidence: 70%
“…Linsenmeier and Zhang, using oxygen-sensitive microelectrodes and oximetry, have found that under both dark and light conditions, the choroidal and retinal circulation could supply, in different proportions, the metabolic demand of photoreceptors 29 . Nesper et al, in a cohort of patients with diabetic retinopathy, have observed using adaptive optics and OCTA photoreceptor changes in areas of capillary dropout in the DCP, suggesting that the integrity of the DCP is needed for photoreceptor metabolism 30 . Assuming that retinal capillaries are present in areas where there is a cellular demand, the small decrease in photoreceptor and INL density towards the periphery could explain the relative stability of the DCP density in this area 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite continuous treatment, the extent of ELM disruption increased, implying that DME must be aggressively treated to prevent continuous degeneration of the outer retina due to chronic, persistent DME and ischaemia (Nesper et al. ).…”
Section: Discussionmentioning
confidence: 99%